From Chalkboards to Keyboards: Exploring the Digital Competence of Educators Rural in Classrooms - Jara, Airene; Pedroso, John Erwin P. (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This research explored the digital competence of secondary school teachers working in rural areas within the New Lucena District, Iloilo Province, focusing on how they acquire, apply, share, and communicate digital knowledge. A descriptive research design was used, involving 82 teachers with both permanent and contractual employment status. Data were gathered using an online survey administered through Google Forms. The tool assessed four key areas of digital competence: Development, Application, Sharing, Knowledge and Communication. Results indicated that these teachers generally possess a moderate level of digital skills. Many expressed confidence in using digital tools for basic tasks, though some aspects, particularly those involving interactive or collaborative applications, remain challenging for them. Descriptive statistics like mean and standard deviation were used to measure both overall digital competence and performance in each specific area. The data suggested that teachers performed best in acquiring and developing digital knowledge, while their weakest point involved using digital platforms for effective communication and teamwork. To check if the differences across these four areas were meaningful, the study made use of the Friedman test, which revealed notable variations. This points to the need for better support in certain aspects of digital skills. In view of these results, the study recommends that professional development initiatives be designed to provide teachers with more practical and hands- on opportunities for digital skills enhancement. Programs that promote peer mentoring, encourage collaborative digital projects, and improve access to up-to-date technological tools and resources could significantly help in bridging the competence gaps.